Ranibizumab Port Delivery System in Neovascular Age-Related Macular Degeneration: Where Do We Stand? Overview of Pharmacokinetics, Clinical Results, and Future Directions - Matteo Mario Carlà; Maria Cristina Savastano; Francesco Boselli; Federico Giannuzzi; Stanislao Rizzo (MDPI AG, 2024)
The ranibizumab (RBZ) port delivery system (PDS) is a device designed to continuously deliver RBZ in the vitreous chamber for the treatment of neovascular age-related macular degeneration (nAMD). It is implanted during a surgical procedure and can provide sustained release of the medication for several months. This review, updated to January 2024, focuses on past clinical studies as well as current and forthcoming trials looking into a PDS with RBZ. In the phase 2 LADDER trial, the mean time to first refill of a PDS with RBZ 100 mg/mL was 15.8 months, with the pharmacokinetic (PK) profile showing a sustained concentration of RBZ in the blood and aqueous humor. More recently, a PDS with RBZ (100 mg/mL) refilled every 24 weeks was shown to be non-inferior to a monthly intravitreal injection (IVI) with RBZ (0.5 mg) over 40 and 92 weeks in the phase 3 ARCHWAY trial. The refill every 24 weeks allowed for a RBZ vitreous exposure within the concentration range of monthly intravitreal injections (IVIs), and the expected half-life (106 days) was comparable with the in vitro results. Nonetheless, vitreous hemorrhage and endophthalmitis were more common side effects in PDS patients. In conclusion, a PDS continuously delivering RBZ has a clinical effectiveness level comparable with IVI treatment. However, a greater frequency of unfavorable occurrences highlights the need for procedure optimization for a wider adoption. Ongoing trials and possible future approaches need to be addressed.